Shellfish utilization and its effect on rocky shore biota in Transkei - Mills, Coleen Gail (Department of Environmental and Geographical Science, 2023)
The shellfish on the rocky shores along the Transkei coast experience intense exploitation from three different sources viz. commercial exploitation, tourist - induced exploitation and continued regular harvesting by the indigenous people. The question raised as a result of these combined factors has been whether or not the rocky shore ecosystem can maintain its balance in the light of the pressure currently been exerted on it. This study sought to investigate all aspects of the shellfish utilization, as well as the effects of this exploitation through a comparison of protected and exploited rocky shore sites. Questionnaire and interview techniques were the primary metacoxal used to assess shellfish utilization. These techniques were backed by personal observations and limited collection and analysis of real remains. The physical sampling of sites by scraping areas in each zone of the rocky shore, followed by the analysis of the samples in the laboratory constituted the main riiethcx:l used to obtain biological data. A photographic technique was also used. The results indicate that the effects of limitation are most obvious in the Perna-coralline algal turf zone, where the exploitation pressure is also the greatest. Perna perna communities in particular are affected. Exploited sites maintain young populations of P. perna with an average size of less than 4crn (Means of 2.95crn and 2.26crn were obtained). The protected sites on the other hand exhibit rrore stable mature communities of P. perna (means of S.91crn and 4.70crn were obtained). An increase in the percentage cover of coralline algal turf and a corrresp:mding decrease in the percentage cover of P. perna was recorded ·with increasing exploitation. Species COIIlp)sition appeared slightly limited in the Perna-coralline algal turf zone The average size of crassostrea cuccblata is reduced. at exploited. sites, (on the basis of percentage cover rreasurementsl .Exploitation could riot be shown to be having any def iriite discernable effects on the limpet populations in all .zones, nor on the variation in species. present or absent in the balanoid and crassostrea zones. The general population structure of mussels at exploited sites has. not d1anged significantly over the last.six years, indicating that a delicate balafice is being maintained. However,. where comrrercial pressure is greatest, as in the vicinity of hotels, this balance . is destroyed and the mussel cormnunity is largely replaced by coralline algal turf (the percentage cover of algal turf at COf fee Bay in the · Perna-coralline algal tur! zone was approx. 91.5%). The existing legislation, maniwer a'7ailability and present control measures pertaining to shellfish utilization are discussed, and general conservation recommendations are trade based on the findings of this study.